identification and prevalence of ectoparasites in milkfish (Chanos chanos) and their relation to the environment in Gampong Bayeun, Aceh Timur - Farlizah, Thasya; Putriningtias, Andika; Komariyah, Sitti (Universitas Halu Oleo, 2023)
Milkfish (Chanos chanos) is one of the main aquaculture commodity species and has an important market value. The rapid development of milkfish cultivation is due to the good performance and growth rate of milkfish. In line with the large number of enthusiasts for fish farming, there are also a number of disturbing problems, thus hindering the development of aquaculture businesses, one of which is infectious diseases caused by parasites. Therefore, the purpose of this study was to identify and determine the prevalence rate of ectoparasites in milkfish (Chanos chanos) in Gampong Bayeun ponds, East Aceh. Sampling was carried out at the Gampong Bayeun pond, East Aceh from 29 August to 9 September 2022 with a total of 90 milkfish samples. Sampling was carried out 9 times. Sampling was carried out when the fish were 2 months old. Identification of ectoparasites was carried out at the Laboratory of the Faculty of Agriculture, Samudra University. The results of this study found three types of ectoparasites that infect milkfish, namely Trichodina sp., (30%), Unitubulotestis sp. (17.8), Dactylogyrus sp., (15.6%). The most common type of parasite found was Trichodina sp., which was found in 278 parasites in milkfish.